Pentingnya Sarapan Dengan Nutrisi Yang Tepat Untuk Daya Tahan Tubuh Anak Di TK Negeri 2 Samarinda - Adam Hasyim Apriansyah (Anakta : Jurnal Pendidikan Islam Anak Usia Dini, 2024)
Nutritious breakfast is an essential habit in supporting endurance, concentration, and readiness to learn among early childhood students. This study aims to explore the breakfast habits of young children at TK Negeri 2 Samarinda and their impact on physical endurance. A descriptive qualitative approach was employed, utilizing data collection techniques such as observation, semi-structured interviews, and document analysis. The subjects of the study were two 6-year-old children, their parents, and the principal of TK Negeri 2 Samarinda. The findings reveal that children with consistent nutritious breakfast habits exhibit higher energy levels, better concentration, and improved readiness to learn compared to children with irregular breakfast patterns. Factors supporting healthy breakfast habits include parental support and school programs such as "Healthy Eating Time," while the main obstacles are picky eating behavior and limited nutritional education. This study highlights the importance of collaboration between parents and schools in fostering healthy breakfast habits to support optimal growth and development in early childhood.